Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpsyg.2021.648883
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Antecedents of Chinese Consumers’ Trust and Distrust

Abstract: To help retailers gain consumers’ trust, many studies have investigated antecedents of consumer trust. However, distrust, a concept closely related to trust, has attracted only sporadic research attention. As a result, whether factors that increase consumer trust can eliminate consumer distrust is unclear. To deepen understanding of trust and distrust, this study applies the critical incident technique to identify and compare the antecedents of trust and distrust of Chinese consumers. The results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 96 publications
(119 reference statements)
0
8
0
Order By: Relevance
“…Some scholars have summarized this and emphasized that the original dimensions that can explain trust mainly include calculation (based on past behavior of the other) and relational (between oneself and another) two trusts (Earle, 2010;Hobbs and Goddard, 2015). Based on the above discussion and the summary of consumer trust in existing literature (Zhao et al, 2021), this study defines consumer trust in a food sales APP platform as "expectations and confidence held by consumers that the APP platform is dependable and can be relied on to deliver offerings on its promises." And believes that consumers' trust in food sales APPs mainly comes from two aspects of psychological recognition and expectation: practical benefits and long-term relationship; this is precisely the focus of psychological contract theory.…”
Section: Consumer Trustmentioning
confidence: 99%
See 2 more Smart Citations
“…Some scholars have summarized this and emphasized that the original dimensions that can explain trust mainly include calculation (based on past behavior of the other) and relational (between oneself and another) two trusts (Earle, 2010;Hobbs and Goddard, 2015). Based on the above discussion and the summary of consumer trust in existing literature (Zhao et al, 2021), this study defines consumer trust in a food sales APP platform as "expectations and confidence held by consumers that the APP platform is dependable and can be relied on to deliver offerings on its promises." And believes that consumers' trust in food sales APPs mainly comes from two aspects of psychological recognition and expectation: practical benefits and long-term relationship; this is precisely the focus of psychological contract theory.…”
Section: Consumer Trustmentioning
confidence: 99%
“…On the other hand, potential risks in the environment have a strong impact on consumer trust (Earle, 2010; Zhao et al ., 2021). In the traditional environment, there are significant differences in consumers' risk perception of different sales channels (Li et al ., 2020).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the unique culture and language of the consumer community can stimulate the empathy of consumers in the community, which has a positive impact on consumers’ tolerance for services and their intention to purchase again ( Wei et al, 2022 ). On the other hand, it can increase consumers’ trust in creators, thereby increasing their sense of trust in the products promoted and carried by creators ( Zhao et al, 2021 ), and then feeding creators back. Rubio et al (2016) once concluded on online consumption that because online shopping promotes competition, increases the comparison of homogeneous products, and reduces the cost for consumers to change decisions, consumers’ loyalty and trust in products are essential for online suppliers ( Rubio et al, 2016 ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“… Rubio et al (2016) once concluded on online consumption that because online shopping promotes competition, increases the comparison of homogeneous products, and reduces the cost for consumers to change decisions, consumers’ loyalty and trust in products are essential for online suppliers ( Rubio et al, 2016 ). The main sources of consumer loyalty and trust include spokesperson, word of mouth, business leader, and business culture ( Zhao et al, 2021 ). The language and culture of the consumer community is a great source of loyalty and trust for consumers.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%